Photoinduced and N-Bromosuccinimide-Initiated Esterification of Aromatic acids and Terminal Alkynes with Alcohols - Liu, Han; Yang, Zhiyong; Yan, Jiaqi; Guo, Jing (Synlett, 2025)
A mild and convenient protocol for the esterification of aromatic acids and terminal alkynes with alcohols by visible-light catalysis strategy using N-bromosuccinimide (NBS) as additive has been developed. This protocol provides access to substituted aromatic esters and α-ketoesters in moderate to good yields at room temperature. The advantage of this method is its operational simplicity compared to other known methods.
Keywords: Esterification; Photocatalysis; N-Bromosuccinimide; Terminal alkynes; α-Ketoesters